2006
DOI: 10.1063/1.2234568
|View full text |Cite
|
Sign up to set email alerts
|

( 2 + 1 ) -dimensional photonic crystals from Langmuir-Blodgett colloidal multilayers

Abstract: Original citationRomanov, S. G., Bardosova, M., Pemble, M. and Torres, C. M. S. Type of publication Article (peer-reviewed)Link to publisher's version

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…No deviation from the diffraction model was observed in the LB crystal, indicating its 1D PBG structure in this wavelength range. Since the sphere monolayers in LB crystals are well ordered, 12 the loss of all but one zero diffraction order in the LB crystal can be explained by the absence of a 3D ordering in its lattice ͓Fig. 1͑b͔͒.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No deviation from the diffraction model was observed in the LB crystal, indicating its 1D PBG structure in this wavelength range. Since the sphere monolayers in LB crystals are well ordered, 12 the loss of all but one zero diffraction order in the LB crystal can be explained by the absence of a 3D ordering in its lattice ͓Fig. 1͑b͔͒.…”
mentioning
confidence: 99%
“…Recently we demonstrated that LB crystals can be described as ͑2+1͒D PhCs. 12 This approach conveniently allows the separation of the spectral range into two parts. The 1D part spans over the wavelength range ഛ2D, where D is the diameter of spheres.…”
mentioning
confidence: 99%
“…3͑a͔͒. The 2L and 5L coatings also possess the transmission minimum centered at 1093 nm due to the Bragg diffraction on a stack of sphere monolayers, 25 which is not shown in Fig. 3.…”
Section: Transmission Versus Emission Spectra Of Sandwich Structmentioning
confidence: 99%
“…2͒. 25,26 Angle-resolved transmission spectra were acquired by illuminating the structures with a collimated 1 mm in diameter beam of a white light from a tungsten lamp at different angles, , of incidence with respect to the film normal. Transmitted light was collected from a cone of about 2°of angular width.…”
Section: Experimental Techniquementioning
confidence: 99%
“…8,9 These minima were associated with excitation of optical eigenmodes of 2D PhC, which propagate in plane of a monolayer. The aim of this work is to demonstrate that similar effect can be observed in thin opal films.…”
mentioning
confidence: 99%